2021
DOI: 10.1186/s13613-021-00959-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between mortality and age among mechanically ventilated COVID-19 patients: a Japanese nationwide COVID-19 database study

Abstract: Background Only a few studies have reported the association between age and mortality in COVID-19 patients who require invasive mechanical ventilation (IMV). We aimed to evaluate the effect of age on COVID-19-related mortality among patients undergoing IMV therapy. Methods This cohort study was conducted using the COVID-19 Registry Japan database, a nationwide multi-centre study of hospitalized patients with laboratory-confirmed COVID-19. Of all 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Although COVID-19 patients with respiratory failure frequently require prolonged IMV support, the inhospital mortality rate has decreased from 30% at the start of the pandemic to below 20% at present [23]. Consistent with large-scale registries of severe COVID-19 [24,25], the median IMV duration was 9 (IQR 6-15) days in the present study, which was markedly longer than in other critically ill patients in the ICU [26]. Previous studies showed that prolonged IMV in patients with acute respiratory failure has detrimental effects on both physical function and mental health [4,5], with a number of sequelae including generalized weakness seen on long-term follow-up, which has been termed as post-intensive care syndrome [27].…”
Section: Discussionmentioning
confidence: 53%
“…Although COVID-19 patients with respiratory failure frequently require prolonged IMV support, the inhospital mortality rate has decreased from 30% at the start of the pandemic to below 20% at present [23]. Consistent with large-scale registries of severe COVID-19 [24,25], the median IMV duration was 9 (IQR 6-15) days in the present study, which was markedly longer than in other critically ill patients in the ICU [26]. Previous studies showed that prolonged IMV in patients with acute respiratory failure has detrimental effects on both physical function and mental health [4,5], with a number of sequelae including generalized weakness seen on long-term follow-up, which has been termed as post-intensive care syndrome [27].…”
Section: Discussionmentioning
confidence: 53%
“…A previous study showed that the COVID-19 severity on admission had a major influence on clinical outcomes, although Japanese patients with COVID-19 demonstrated fewer comorbidities and a trend toward lower mortality 21,22) . Another study evaluating patients with severe COVID-19 requiring mechanical ventilation reported that older patients showed a high mortality rate of 49.7% in the 80s and 83.3% in the 90s 23) . In line with the previous report, the current study revealed that old age showed a significantly higher risk of all-cause death irrespective of COVID-19 severity on admission, and patients with severe COVID-19 over 80 showed a quite high mortality rate of 85.7%.…”
Section: Discussionmentioning
confidence: 99%
“…In our assessment of organ dysfunction at hospital discharge, the median SOFA score was 1, and most of the patients were free from organ support. In previous studies reporting respiratory failure at hospital discharge in COVID-19 patients supported by MV, approximately 50% of the patients required supplemental oxygen therapy at discharge [ 18 , 41 ]. Although it is difficult to simply compare the studies for the recovery from respiratory failure owing to variation in the timing of assessment, the novelty in our findings is that most survivors recovered to be free from supplemental oxygen therapy within a few weeks after liberation from MV.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese nationwide multicenter registry study, which included 1,555 mechanically ventilated COVID-19 patients registered between January 1, 2020, and February 28, 2021, from 925 participating hospitals throughout Japan, reported in-hospital mortality of 26% [ 41 ]. Given the equivalent study period and patient backgrounds, such as age, sex, and underlying diseases, in our and the aforementioned study, the in-hospital mortality of 21% in our study would be comparable to that study.…”
Section: Discussionmentioning
confidence: 99%